Dampak Ekonomi Kebijakan Larangan Kegiatan bagi Siswa Akhir SMA di Jawa Barat dalam Perspektif Maqasid Syariah - Siti Meisah; Kisanda Midisen; MH Ainulyaqin; Sukron Mamun; Yudianto Achmad (Jurnal Ilmiah Ekonomi Islam, 2026)
Ceremonial and costly activities for high school seniors often place an economic burden on parents and contribute to social inequality. Therefore, the government has enacted a policy banning such activities. This study aims to analyze the implementation of the policy banning high school senior activities at SMA Negeri 1 Cikarang Pusat and its economic impact from the perspective of Maqasid Syariah. The research method used is a qualitative approach employing interview and observation techniques. The results indicate that the ban policy has been effectively implemented through outreach and adjustments to the school program, yielding positive economic impacts, including reduced financial burdens, increased efficiency, and the promotion of economic justice. From the perspective of Maqasid Syariah, this policy aligns with the principles of hifz al-mal, hifz al-nafs, and hifz al-‘aql. Thus, this policy is effective in implementation, has a positive economic impact, and is consistent with the principle of public interest.